Studies in Health Technology and Informatics Volume 11 - Low Vision Research and New Developments in Rehabilitation - Looijestijn, P.L. (IOS Press, 2014)
Today society places more demands on seeing and processing of visual information than ever before. Information is given increasingly in a visual way and with a great diversity like traffic signs, high definition computer monitors, newspapers, books, television, LCD control panels, etcetera. The expanding flow of visual information places a considerable demand on visual processing in the occupational as well as in daily life conditions. As a consequence people with a decreased visual performance will be confronted sooner than before with their disabilities, which can result in a handicap. More than in the past rehabilitation is aimed at using the visual potential of the visually impaired person and the visual function has to be restored to a higher degree of performance in order to cope with the higher visual demands in daily life. It requires a thorough knowledge of the visual system and visual rehabilitation. This knowledge can only be extended by interdisciplinary cooperation: rehabilitation therapist, optometrist, occupational therapist, ophthalmologist, educationist, psychologist, clinical physicist; all of them have professional knowledge in the field. Some possess a large amount of empirical knowledge, other are more educated in the theoretical aspects of vision and visual impairment.